Systematic Literature Review: Pengaplikasian Metode Pembelajaran Dalam Pembelajaran Bahasa Indonesia Di Pendidikan Dasar Dalam Meningkatkan Hasil Belajar Siswa - Ni Putu Diah Setiarini; Putu Vina Aryadnyani; I Gusti Agung Ayu Putu Listyana; Ni Kadek Krisnadewi; Ketut Novitayanti; I Made Krisna Bayu; Ida Bagus Putrayasa; Ni Ketut Desia Tristiantari (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the effectiveness of various instructional methods in improving Indonesian language learning outcomes among elementary school students. Despite the implementation of diverse teaching approaches, findings on their effectiveness remain fragmented, necessitating a systematic review. The research employed the Systematic Literature Review (SLR) method based on PRISMA guidelines, including identification, screening, eligibility assessment, and study inclusion stages. Data were collected from Google Scholar, SINTA, and accredited national journals. From 45 initially identified articles, 10 studies meeting the inclusion criteria were selected for analysis. Data collection used document analysis with a literature extraction sheet, while analysis was conducted through descriptive and comparative content analysis techniques. The findings reveal that instructional methods such as role playing, project-based learning, problem-based learning, storytelling, demonstration, and jigsaw cooperative learning consistently improve students’ learning outcomes. These improvements include cognitive achievement, speaking skills, learning motivation, participation, and engagement in the learning process. The study concludes that selecting instructional methods suited to students’ characteristics and learning materials is essential for enhancing the quality of Indonesian language instruction in elementary schools.